1995
DOI: 10.1091/mbc.6.9.1215
|View full text |Cite
|
Sign up to set email alerts
|

Vinblastine suppresses dynamics of individual microtubules in living interphase cells.

Abstract: We have characterized the effects of vinblastine on the dynamic instability behavior of individual microtubules in living BS-C-1 cells microinjected with rhodamine-labeled tubulin and have found that at low concentrations (3-64 nM), vinblastine potently suppresses dynamic instability without causing net microtubule depolymerization. Vinblastine suppressed the rates of microtubule growth and shortening, and decreased the frequency of transitions from growth or pause to shortening, also called catastrophe. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
148
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(157 citation statements)
references
References 56 publications
9
148
0
Order By: Relevance
“…These cells were also partially cross-resistant to paclitaxel. In this study, we observed an increase in P. (Jordan et al, 1992;Derry et al, 1995;Dhamodharan et al, 1995). Using purified 0-tubulin isotypes, Panda et al (1994) have shown that microtubule dynamics are regulated by the tubulin isotype composition.…”
Section: Discussionsupporting
confidence: 57%
“…These cells were also partially cross-resistant to paclitaxel. In this study, we observed an increase in P. (Jordan et al, 1992;Derry et al, 1995;Dhamodharan et al, 1995). Using purified 0-tubulin isotypes, Panda et al (1994) have shown that microtubule dynamics are regulated by the tubulin isotype composition.…”
Section: Discussionsupporting
confidence: 57%
“…Because antimicrotubule agents are widely used in cancer therapy, tubulin isotype composition of tumour cells may be an important factor in the success of therapy. Estramustine, vinblastine and paclitaxel have been shown to suppress microtubule dynamics at very low drug concentrations (Jordan et al, 1993(Jordan et al, , 1996Dhamodharan et al, 1995;Panda et al, 1997). Work by Lu and Luduena (1993) demonstrated that microtubules lacking the β III isotype polymerized at a faster rate in the presence of paclitaxel than the microtubules from unfractioned tubulin.…”
Section: Discussionmentioning
confidence: 99%
“…This enhanced stability may also explain the large increase in average microtubule length. Based upon in vitro experiments, it has been postulated that animal MAPs stimulate the growth of microtubules not by increasing the rate of polymerization but by decreasing disassembly (7,26,27). The dilution experiments showed that disassembly of microtubules was markedly slower in the presence of MAP60, which may therefore stimulate microtubule growth in the same way neuronal MAPs do, that is, by decreasing disassembly.…”
Section: Discussionmentioning
confidence: 99%